Plasticity and stability of potato varieties bred by Falenki breeding station - N. F. Sintsova; Z. F. Sergeeva; O. N. Bashlakova (Аграрная наука Евро-Северо-Востока, 2018)
Studies were done in two locations: on experimental fields of Falenki breeding station (s. Falenki, Kirov region, Russia) and in Federal Agricultural Research Center of North-East (FARC North East, Kirov, Russia) in 2014-2017. Ten new varieties bred in Falenki breeding station were investigated. An average productivity for two locations of ecological test during four years was 26.5 t/ha; on Falenki station's field - 30.1 t/ha; on FARC's field -22.98 t/ha. According to average productivity, early varieties 170-08 and 179-10 had addition yield as compared to standard variety Udacha 1.4 and 1.0 t/ha correspondingly. Middle-early varieties 27-07, 455-08, and 90-09 exceeded standard variety Nevsky on 5.2...3.5 t/ha. Influence of factor "location", which is part in total phenotypic variability of productivity was 15.8%. Dependence of potato productivity variation on weather conditions of growing season was 64.4%; part of genotype influence - 4.6%. Estimation of values of plasticity bi and stability Si2 allowed to select varieties 170-08 and 179-10 with high phenotypic reaction of genotype to amelioration of growing conditions. Variety 179-10 could be accepted as variety of intensive type (bi = 1.29) with high level of stability (Si2 = 5.42). Variety 170-08 according to Si2 = 4.30 has the most stabile yield within the investigated set of varieties. Variety 455-08 has high calculated stability of production (Si2 = 5.04). Thus, varieties 170-08 and 179-10 have optimal combination of productivity and adaptation parameters.